THE EFFECTS OF DIRECTED READING THINKING ACTIVITY (DRTA) METHOD TOWARDS THE ABILITY OF THE FIRST YEAR STUDENTS OF SMA NEGERI 10 PEKANBARU IN COMPREHENDING READING TEXT - Sri Murti Handayani Murti Handayani; Erni '; Mahdum ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This one shot pre-test post-test design was aimedto find out the effects of Directed Reading Thinking Activity (DRTA)method towards the ability of the first year students of SMA N 10Pekanbaru in comprehending text. This study answered thefollowing research question:”is there any significant effect DRTAmethod to reading comprehension achievement of the first yearstudents of SMA N 10 Pekanbaru in comprehending text?”Theparticipants were 36 students of the first year students of SMANegeri 10 Pekanbaru. The time of this research was on academic2014-2015, from august - October at SMA N 10 Pekanbaru. Thisschool is located on St.bukitbarisan, Pekanbaru. The data wascollected by using pre-test and post-test. The data was analyzed byusing SPSS Aplication. The research finding of this research showedthat there is significant effect of Directed Reading Thinking Activitytowards the ability of the first year students of SMA N 10 Pekanbaruin comprehending reading text.the finding also proved that in thepre-test students’ average score was 6.82 and after the treatmentapplied there is contribution in post-test score 0.74.Keywords: Directed Reading Thinking Activity (DRTA), Comprehending Reading Text,one shot pre-test post-test design.